Molecular, genetic, and nutritional aspects of major and trace minerals - TotalBoox; TBX ([Place of publication not identified] : Elsevier Science, 2016)
Molecular, Genetic, and Nutritional Aspects of Major and Trace Minerals is a unique reference that provides a complete overview of the non-vitamin micronutrients, including calcium, copper, iodine, iron, magnesium, manganese, molybdenum, phosphorus, potassium, selenium, sodium, and zinc. In addition, the book covers the nutritional and toxicological properties of nonessential minerals chromium, fluoride and boron, and silicon and vanadium, as well as ultra-trace minerals and those with no established dietary requirement for humans. Users will find in-depth chapters on each essential mineral and mineral metabolism, along with discussions of dietary recommendations in the United States and around the world. Presents the only scientific reference to cover all of the nutritionally relevant essential major and trace minerals Provides a broad introductory chapter on each mineral to give readers valuable background and context Clarifies the cellular and molecular aspects of each mineral and its genetic and genomic aspects Includes coverage of all nutritionally relevant minerals--essential major trace minerals and ultra-trace minerals Underscores the important interactions between minerals so readers learn how metabolism of one mineral influences another.
Adipocyte Fat MetabolismEndoplasmic Reticulum Stress and Inflammation; Novel Adipose-Derived Mediators; Insulin Signaling; CONCLUSION; REFERENCES; 5 -- Calcium: Basic Nutritional Aspects; INTRODUCTION; Functions of Calcium; Calcium Homeostasis, Vitamin D, and Parathyroid Hormone; Dietary Calcium Requirements; Skeletal Health; Bone Density; Fractures; Falls; Cardiovascular Disease; Preeclampsia and Hypertension in Pregnancy; Cancer; Calcium and the Kidney; Renal Stones; Mortality; Source of Calcium: Does It Matter?; Recommendations for Dietary Calcium Intakes; Calcium Intakes.
Vendor-supplied metadata.
Keywords: Trace elements in nutrition; Trace elements -- Physiological effect; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Preventive Medicine; Trace elements in nutrition; Trace elements -- Physiological effect; Electronic books